Beta‐lactam plus macrolides or beta‐lactam alone for community‐acquired pneumonia: A systematic review and meta‐analysis. Issue 7 (23rd June 2016) - Horita, Nobuyuki; Otsuka, Tatsuya; Haranaga, Shusaku; Namkoong, Ho; Miki, Makoto; Miyashita, Naoyuki; Higa, Futoshi; Takahashi, Hiroshi; Yoshida, Masahiro; Kohno, Shigeru; Kaneko, Takeshi
Abstract: It is unclear whether in the treatment of community‐acquired pneumonia (CAP) beta‐lactam plus macrolide antibiotics lead to better survival than beta‐lactam alone. We report a systematic review and meta‐analysis. Trials and observational studies published in English were included, if they provided sufficient data on odds ratio for all‐cause mortality for a beta‐lactam plus macrolide regimen compared with beta‐lactam alone. Two investigators independently searched for eligible articles. Of 514 articles screened, 14 were included: two open‐label randomized controlled trials (RCTs) comprising 1975 patients, one non‐RCT interventional study comprising 1011 patients and 11 observational studies comprising 33 332 patients. Random‐model meta‐analysis yielded an odds ratio for all‐cause death for beta‐lactam plus macrolide compared with beta‐lactam alone of 0.80 (95% CI 0.69–0.92, P  = 0.002) with substantial heterogeneity ( I 2  = 59%, P for heterogeneity = 0.002). Severity‐based subgroup analysis and meta‐regression revealed that adding macrolide had a favourable effect on mortality only for severe CAP. Of the two RCTs, one suggested that macrolide plus beta‐lactam lead to better outcome compared with beta‐lactam alone, while the other did not. Subgrouping based on study design, that is, RCT versus non‐RCT, which was almost identical to subgrouping based on severity, revealed substantial inter‐subgroup heterogeneity. Compared with beta‐lactam alone, beta‐lactam plus macrolide may decrease all‐cause death only for severe CAP. However, this conclusion is tentative because this was based mainly on observational studies.